Mediální gramotnost v digitálním věku: Etnické a národnostní stereotypy v médiích a jejich vliv na středoškolskou mládež - Truhlářová, Jana (Univerzita Karlova, Fakulta sociálních věd, 2023)
This bachelor's thesis examines the influence of the media on youth and explores it through the focus on ethnic and national stereotypes in the media. Through a quantitative method of questionnaire survey distributed among high school students in the Karviná region, it examines the ways of media consumption, experiences with media representation of ethnic and national minorities, as well as attitudes towards the represented reality. It also examines how students themselves perceive the influence of the media and what media and digital literacy tools they are aware of themselves. The theoretical part of the thesis focuses on the current state of media influence on youth, ethnic and national stereotype theory and digital literacy. The practical part is devoted to the analysis and presentation of the results of the questionnaire survey. Tato bakalářská práce se zabývá vlivem médií na mládež a zkoumá je na případu etnických a národnostních stereotypů v médiích. Prostřednictvím kvantitativní metody dotazníkového šetření distribuovaného mezi studenty středních škol na Karvinsku zkoumá způsoby konzumace médií, zkušenosti s mediální reprezentací etnických a národnostních menšin a zároveň postoje k reprezentované realitě. Současně zkoumá, jak sami studenti vnímají vliv médií a jaké nástroje mediální a digitální gramotnosti znají nebo sami využívají. Teoretická část práce se zaměřuje na současný stav problematiky vlivu médií na mládež, teorii etnických a národnostních stereotypů a digitální gramotnost. Praktická část se věnuje analýze a prezentaci výsledků dotazníkového šetření. Katedra mediálních studií Department of Media Studies Faculty of Social Sciences Fakulta sociálních věd